2002
DOI: 10.1111/j.1151-2916.2002.tb00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Zinc Oxide: From Green to Sintered State

Abstract: The thermal conductivity of ZnO with different particle sizes (micrometer, submicrometer, and nanometer) was measured using the laser flash technique. As the "green" samples were heated from room temperature to 600°C (and 1000°C) and then cooled down to room temperature, the thermal conductivity was measured in situ. A model for interparticle neck growth was developed based on mass transfer to the neck region of a powder as a result of known temperature. By combining this model with a three-dimensional numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
52
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 22 publications
9
52
0
1
Order By: Relevance
“…Wurtzite zinc oxide (ZnO) is another well-characterized system. Olorunyolemi et al 91 and Barrado et al 92 reported κ ' of polycrystalline ZnO with an average particle size of 20 and 1000 nm, respectively. AAPL, performed with average grain size of 500 nm, is in very good agreement with the experimental results capturing the effects of the grain boundaries' scattering (Fig.…”
Section: Validation With Experimentsmentioning
confidence: 99%
“…Wurtzite zinc oxide (ZnO) is another well-characterized system. Olorunyolemi et al 91 and Barrado et al 92 reported κ ' of polycrystalline ZnO with an average particle size of 20 and 1000 nm, respectively. AAPL, performed with average grain size of 500 nm, is in very good agreement with the experimental results capturing the effects of the grain boundaries' scattering (Fig.…”
Section: Validation With Experimentsmentioning
confidence: 99%
“…At t = 0 the surface temperature at z = 0 is instantaneously raised to a constant temperature T S . Using the results of measurements of the thermal conductivity in ZnO [3], we can formulate the problem by writing…”
Section: · Heat Transfer In Znomentioning
confidence: 99%
“…This article aims to show that Bürmann's theorem can serve as a powerful tool for gaining approximations fulfilling such demands. We have chosen canonical examples [1,2,3] from the field of linear and nonlinear heat transfer to illustrate this technique.…”
Section: ‡ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] The bulk value of s for ZnO equal to 0.1 J m À2 is used. [17] The dependence of S on the reactor temperature is shown in Figure 1b. It can be noticed that the partial pressure of ZnO monomer ( p) becomes constant after 500 8C.…”
mentioning
confidence: 98%